2014
DOI: 10.1016/j.immuni.2014.09.008
|View full text |Cite
|
Sign up to set email alerts
|

HIF Transcription Factors, Inflammation, and Immunity

Abstract: The hypoxic response in cells and tissues is mediated by the family of hypoxia-inducible factor (HIF) transcription factors that play an integral role in the metabolic changes that drive cellular adaptation to low oxygen availability. HIF expression and stabilization in immune cells can be triggered by hypoxia, but also by other factors associated with pathological stress: e.g., inflammation, infectious microorganisms, and cancer. HIF induces a number of aspects of host immune function, from boosting phagocyte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
861
2
14

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 986 publications
(898 citation statements)
references
References 116 publications
21
861
2
14
Order By: Relevance
“…The expression of the transcription factor HIF‐1α is elevated in response to low‐oxygen conditions. HIF‐1α is involved in multiple cellular functions, including blood vessel formation, cell proliferation, immunity and inflammatory responses 6, 7. As shown in our previous studies, HIF‐1α expression is significantly increased in PQ‐treated rat lung tissues, and EMT is also observed.…”
Section: Introductionmentioning
confidence: 63%
“…The expression of the transcription factor HIF‐1α is elevated in response to low‐oxygen conditions. HIF‐1α is involved in multiple cellular functions, including blood vessel formation, cell proliferation, immunity and inflammatory responses 6, 7. As shown in our previous studies, HIF‐1α expression is significantly increased in PQ‐treated rat lung tissues, and EMT is also observed.…”
Section: Introductionmentioning
confidence: 63%
“…Although the impact of HIFs on immune responses has been observed (39), the mechanisms by which VHL affects the cellular immunity response, either directly or through HIFs, is still largely unknown. Interestingly, it was reported that pVHL could inhibit NF-kB phosphorylation through its effect on the NF-kB agonist Card 9, which links pVHL to control of NF-kB activity and tumorigenesis (40).…”
Section: Discussionmentioning
confidence: 99%
“…Another crucial player is HIF-1, a well-studied transcriptional factor inducing VEGF production and conveying resistance for antitumor drugs (40). Beyond its role in angiogenesis, HIF has been shown to regulate, and be regulated by, many metabolic and inflammatory mediators, including mTOR (11,41,42). Everolimus-mediated blockage of mTOR activity may downregulate HIF-1 function, potentially impacting bevacizumab resistance.…”
Section: Discussionmentioning
confidence: 99%